RELATIVE CONDITION FACTOR AND FOOD AND FEEDING HABITS OF TWO ARIID CATFISHES FROM MUMBAI WATERS - Deo, A. D.; Venkateshvaran, K.; Devaraj, M. (Journal of Indian Fisheries Association, 2010)
Condition factor based on length-weight relationship and food and feeding habits of Arius dussumieri (Black lip sea catfish) and Osteogeneiosus militaris (Soldier catfish) from the Mumbai coast have been studied. Relative Condition Factor showed variations on a monthly basis, and appear to be influenced by feeding and breeding activities. Both the species studied are carnivorous bottom feeders, with crustaceans followed by other smaller fishes forming the major food item in the gut contents.Â Key words: Relative condition factor, Food and feeding habits, Ariid catfishes. Â